2017
DOI: 10.1038/s41419-017-0086-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagy delays motoneuron degeneration and extends lifespan in a mouse model of spinal muscular atrophy

Abstract: Spinal muscular atrophy (SMA) is a recessive autosomal neuromuscular disease, due to homozygous mutations or deletions in the telomeric survival motoneuron gene 1 (SMN1). SMA is characterized by motor impairment, muscle atrophy, and premature death following motor neuron (MN) degeneration. Emerging evidence suggests that dysregulation of autophagy contributes to MN degeneration. We here investigated the role of autophagy in the SMNdelta7 mouse model of SMA II (intermediate form of the disease) which leads to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 73 publications
5
58
0
Order By: Relevance
“…According to the literature (Branchu et al, 2013 ; Biondi et al, 2015 ; Genabai et al, 2015 ), these data confirm that JNK-signaling pathway is activated in SMA MNs and is probably involved in neuronal cell death. Indeed, confirming previous observations (d’Errico et al, 2013 ; Piras et al, 2017 ), here we report the reduction in the density of MNs in SMA spinal cord compared to WT group (WT PBS = 1,651.14 ± 90.3 cells/mm 3 ; SMA PBS = 891.22 ± 82.5 cells/mm 3 ; Mann-Whitney test, p = 0.0043; Figures 2A,A′,B ). As a consequence of neurodegeneration, proximal muscles of SMA mice are early affected by atrophy (Valsecchi et al, 2015 ; Boido et al, 2018 ): indeed, quadriceps fibers showed reduced area (WT PBS = 578.4 ± 80.8 μm 2 ; SMA PBS = 297.7 ± 31.7 μm 2 ; unpaired t -test, p = 0.043; Figures 2C,C′,D ), perimeter (WT PBS = 90.8 ± 7.1 μm; SMA PBS = 76.2 ± 1.9 μm; unpaired t -test, p = 0.036; Figure 2E ), maximal (WT PBS = 32.4 ± 1.7 μm; SMA PBS = 28.04 ± 0.78 μm; unpaired t -test, p < 0.001) and minimal Feret’s diameter (WT PBS = 22.8 ± 1.4 μm; SMA PBS = 16.7 ± 0.85 μm; unpaired t -test, p < 0.001; Figure 2F ).…”
Section: Resultssupporting
confidence: 91%
“…According to the literature (Branchu et al, 2013 ; Biondi et al, 2015 ; Genabai et al, 2015 ), these data confirm that JNK-signaling pathway is activated in SMA MNs and is probably involved in neuronal cell death. Indeed, confirming previous observations (d’Errico et al, 2013 ; Piras et al, 2017 ), here we report the reduction in the density of MNs in SMA spinal cord compared to WT group (WT PBS = 1,651.14 ± 90.3 cells/mm 3 ; SMA PBS = 891.22 ± 82.5 cells/mm 3 ; Mann-Whitney test, p = 0.0043; Figures 2A,A′,B ). As a consequence of neurodegeneration, proximal muscles of SMA mice are early affected by atrophy (Valsecchi et al, 2015 ; Boido et al, 2018 ): indeed, quadriceps fibers showed reduced area (WT PBS = 578.4 ± 80.8 μm 2 ; SMA PBS = 297.7 ± 31.7 μm 2 ; unpaired t -test, p = 0.043; Figures 2C,C′,D ), perimeter (WT PBS = 90.8 ± 7.1 μm; SMA PBS = 76.2 ± 1.9 μm; unpaired t -test, p = 0.036; Figure 2E ), maximal (WT PBS = 32.4 ± 1.7 μm; SMA PBS = 28.04 ± 0.78 μm; unpaired t -test, p < 0.001) and minimal Feret’s diameter (WT PBS = 22.8 ± 1.4 μm; SMA PBS = 16.7 ± 0.85 μm; unpaired t -test, p < 0.001; Figure 2F ).…”
Section: Resultssupporting
confidence: 91%
“…We observed that this defect was accompanied by increased levels of p62 and ubiquitinated proteins and that an acute decrease in SMN protein levels produced the same results. Our findings agree with those of recent studies that reported autophagy alterations upon SMN downregulation in cell lines (50,67,68) and answer the previously unresolved question of why autophagy is dysfunctional in SMA and explain the nature of the interplay between SMN and autophagy activity. We postulate that, as a consequence of SMN deficiency-induced autophagy impairment, ubiquitinated proteins and p62 accumulate.…”
Section: Methodssupporting
confidence: 93%
“…Recent studies have shown that Stasimon is an ER-resident, six-transmembrane-pass protein that is essential for mouse embryonic development (Van Alstyne et al, 2018b) and functions in autophagy (Moretti et al, 2018;Morita et al, 2018;Shoemaker et al, 2019). There have also been reports of autophagy dysregulation in SMA, but there is disagreement about whether this pathway is inhibited (Custer and Androphy, 2014;Periyakaruppiah et al, 2016;Rodriguez-Muela et al, 2018) or stimulated (Gonç alves et al, 2018;Piras et al, 2017) by SMN deficiency. Therefore, although autophagy inhibition has been shown to ameliorate the phenotype of SMA mice by blocking p62-mediated SMN degradation (Rodriguez-Muela et al, 2018), it remains to be established whether autophagy defects directly contribute to SMA pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Stasimon Deficiency Is Sufficient to Induce p53 S18 Phosphorylation Recent studies have shown that Stasimon is required for autophagy in cultured mammalian cells (Moretti et al, 2018;Morita et al, 2018;Shoemaker et al, 2019). There have also been reports of autophagy dysregulation in SMA (Custer and Androphy, 2014;Gonç alves et al, 2018;Periyakaruppiah et al, 2016;Piras et al, 2017;Rodriguez-Muela et al, 2018). Therefore, we sought to investigate the possible involvement of Stasimon-dependent autophagy defects in SMA pathogenesis.…”
Section: Stasimon Contributes To Motor Neuron Degeneration In Sma Micementioning
confidence: 99%